Removal of isoproturon from aqueous solution by ZSM-5 zeolite - Hgeig Ali Mohammed; Novaković Mladenka; Petrović Maja; Mihajlović Ivana; International Symposium on Analytical and Environmental Problems (24.) (2018) (Szeged) (2018)
ZSM-5 zeolite was used to remove isoproturon pesticide from aqueous solutions. The main parameters of adsorption process such as dosages of adsorbent, contact time and initial concentration of isoproturon were investigated. Adsorption equilibrium studies were carried out in batch systems. Results were modeled by adsorption isotherms: Langmuir, Freundlich and Temkin isotherms. The best correlation was achieved with Temkin adsorption isotherm. The maximum adsorption capacity of isoproturon calculated from the Langmuir isotherm was 4,12 mg g-1 at room temperature. Adsorption kinetics of isoproturon has been studied by commonly used kinetic models, i.e., the pseudo-first-order model, the pseudo-second-order model and the intraparticle diffusion model. The kinetic modeling studies showed that kinetics of isoproturon on Zeolite ZSM-5 followed the model of pseudo - second order. This study proved that ZSM-5 zeolite could be used for the removal of isoproturon from aqueous media.